Investigation of hydrodynamic impact on an unevenly buried pipeline in a permeable bottom - D. Yu. Sherstnev; Yu. V. Bryanskaya (Stroitel’stvo: Nauka i Obrazovanie, 2023)
Introduction. When designing pipeline crossings for various purposes, the solution of many engineering problems is associated with the calculation of velocity distribution and estimation of hydraulic resistance created by them. Since it is very difficult to estimate the value of hydrodynamic resistance coefficients and lifting force by theoretical means, experimental studies are usually resorted to. Pipelines can be positioned in different ways in relation to the flow, and in practice pipelines are also buried in the bottom of the watercourse. In physical experiments, a partially buried pipeline is often modelled by truncating the buried section of the pipeline. This experimental setup is more suitable for a pipeline located in an impermeable bottom. In reality, erosion-prone bottoms are often porous and permeable.Materials and methods. Hydrodynamic forces acting on a pipeline with uneven depth on both sides, on a permeable bottom, are numerically studied. Two-dimensional Navier – Stokes equations averaged over Reynolds with k–e turbulence model are used to simulate fluid flow. The seepage flow at the permeable bottom is assumed to obey Darcy’s law, the Laplace equation is solved to calculate the pore pressure assuming an isotropic and homogeneous bottom. The flow structure and pressure distribution around the pipeline are considered. The ANSYS Fluent software package is used for numerical modelling.Results. It was found that the flow structure around the pipeline is asymmetric due to the difference in bottom levels on the two sides of the pipeline. The process of scouring of the sandy bottom in the area of the pipeline location was modelled in ANSYS Fluent. Comparison of calculation results at different flow rates was made. It was found that there is an obvious difference between the hydrodynamic forces experienced by the pipeline due to the asymmetric flow structure around the pipeline.Conclusions. Peak values of external forces and lift force decreasing as the value of depth into the bottom behind the pipeline increases (e2/D). The maximum error of the drag and lift forces calculated using sixth order Fourier series is about 4 %.